How a parish conflict influenced the debate on Argentine secularism: the dismissal of the priest of San Cristóbal in 1886 and its unexpected implications - Di Stefano, Roberto (2022)
In Argentine history, the 1880s are famous for the public debate around the definition of secularism. In that decade, three legislative projects were discussed and promulgated, giving form to the «secular laws» of education, civil registration, and civil marriage. In 1886, a trivial conflict between a parish priest from the suburbs of Buenos Aires and the archbishop fueled a confrontation that reached the highest political and ecclesiastical spheres, attracted the attention of leading public figures, and even led to the adoption of relevant legislation measures. The story of that episode is interesting because it put on the table crucial issues that defined secularism; shows how a fortuitous event, initially inconsequential, can acquire importance in decision-making at the highest level; illustrates the intricate relationships that mediate between events, conjunctures, and structural transformations; and informs about the dialectical links between discourses and their contexts of enunciation.